Toward an optimal oligosaccharide ligand for rat natural killer cell activation receptor NKR-P1 - Krist, P; Herkommerová-Rajnochová, E; Rauvolfová, J; Semenuk, T; Vavrusková, P; Pavlícek, J; Bezouska, K; Petrus, L; Kren, V (Biochemical and biophysical research communications, 2001)
Aminosugars have a good affinity for the NKR-P1A protein, the major activating receptor at the surface of rat natural killer cells. We have systematically investigated the structural requirements of the recombinant soluble dimeric form of the receptor for its optimal carbohydrate ligands. While N-acetylD-mannosamine was the best neutral monosaccharide ligand, its participation in the context of an extended oligosaccharide sequence was equally important. The IC(50) value for the GalNAcbeta1 --> ManNAc disaccharide was nearly 10(-10) M with a further possible increase depending on the type of the glycosidic linkage and the aglycon nature. From the point of view of its availability, stability, and affinity for the receptor and a potential in vivo use, these studies are pivotal for the design of an oligosaccharide or glycomimetics suitable for further clustering into the multivalent glycodendrimers.
Keywords: lektiny typu C; Oligosaccharides; Carbohydrates; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; sacharidy; Carbohydrate Conformation; Antigens, Surface; antigeny povrchové; krysa rodu Rattus; Lectins, C-Type; Recombinant Proteins; zvířata; buňky NK; Killer Cells, Natural; NK Cell Lectin-Like Receptor Subfamily B; Protein Folding; rekombinantní proteiny; sbalování proteinů; oligosacharidy; Rats; lektinové receptory NK-buněk - podrodina B; Animals; konformace sacharidů